Hester Baer and Alexandra Merley Hill, eds. German Women’s Writing in the Twenty-First Century. Rochester: Camden House, 2015. - Brigitte Rossbacher (Studies in 20th & 21st Century Literature, 2018)
Review of Hester Baer and Alexandra Merley Hill, eds. German Women’s Writing in the Twenty-First Century. Rochester: Camden House, 2015. Note: a member of the editorial staff for STTCL is mentioned in this review. This staff member was not involved in the solicitation or preparation of this review.
Keywords: German women' s writing; twenty-first century